2014
DOI: 10.1074/mcp.m113.037085
|View full text |Cite
|
Sign up to set email alerts
|

Specific Glycosylation of Membrane Proteins in Epithelial Ovarian Cancer Cell Lines: Glycan Structures Reflect Gene Expression and DNA Methylation Status

Abstract: Epithelial ovarian cancer is the fifth most common cause of cancer in women worldwide bearing the highest mortality rate among all gynecological cancers. Cell membrane glycans mediate various cellular processes such as cell signaling and become altered during carcinogenesis. The extent to which glycosylation changes are influenced by aberrant regulation of gene expression is nearly unknown for ovarian cancer and remains crucial in understanding the development and progression of this disease. To address this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
153
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(166 citation statements)
references
References 82 publications
12
153
0
1
Order By: Relevance
“…Saladova et al, reported specific N-glycosylation changes on serum glycoproteins from ovarian cancer patients, including a decrease in galactosylation of IgG and an increase in sialyl Lewis X (SLe(x) on haptoglobin beta-chain, alpha1-acid glycoprotein and alpha1-antichymotrypsin (30). We have also observed membrane glycosylation changes between non-cancerous ovarian surface epithelial (HOSE 6.3 and HOSE 17.1) and serous ovarian cancer cell lines (SKOV 3, IGROV1, A2780, and OVCAR3) (31). The "bisecting N-acetyl-glucosamine" type N-glycans, increased levels of ␣ 2-6 sialylated N-glycans and "N,NЈ-diacetyl-lactosamine" type N-glycans were predominantly observed in serous ovarian cancer cell lines while absent in the noncancerous ovarian cells.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Saladova et al, reported specific N-glycosylation changes on serum glycoproteins from ovarian cancer patients, including a decrease in galactosylation of IgG and an increase in sialyl Lewis X (SLe(x) on haptoglobin beta-chain, alpha1-acid glycoprotein and alpha1-antichymotrypsin (30). We have also observed membrane glycosylation changes between non-cancerous ovarian surface epithelial (HOSE 6.3 and HOSE 17.1) and serous ovarian cancer cell lines (SKOV 3, IGROV1, A2780, and OVCAR3) (31). The "bisecting N-acetyl-glucosamine" type N-glycans, increased levels of ␣ 2-6 sialylated N-glycans and "N,NЈ-diacetyl-lactosamine" type N-glycans were predominantly observed in serous ovarian cancer cell lines while absent in the noncancerous ovarian cells.…”
mentioning
confidence: 62%
“…The agalactosylated bisecting structure of m/z 1339.4 was observed only in the necrotic tissue of the sample P1. 2-6 sialic acids were differentiated based on the chromatographic behavior and retention times of previous studies (31,38,39). Detailed structural characterization of the N-glycans was carried out by tandem MS fragmentation analysis.…”
Section: Resultsmentioning
confidence: 99%
“…cellular mRNA) levels are often used as a key indicator of what glycogenes are being translated and the levels of biosynthetic enzymes and glycans that result, the relationship is not straightforward. A number of investigators have attempted to relate transcript levels to glycoenzyme activity and carbohydrate structures, including the response of the system to perturbations [11,2426]. Such studies have been conducted using human promyelocytic leukocytes differentiated to primary neutrophils [24], a limited panel of mouse tissue [11], mouse embryonic stem cells differentiated to embryoid bodies and endodermal cells [25], and epithelial ovarian cancer cell types [26].…”
Section: Multi-level Regulation Of Glycosylationmentioning
confidence: 99%
“…A number of investigators have attempted to relate transcript levels to glycoenzyme activity and carbohydrate structures, including the response of the system to perturbations [11,2426]. Such studies have been conducted using human promyelocytic leukocytes differentiated to primary neutrophils [24], a limited panel of mouse tissue [11], mouse embryonic stem cells differentiated to embryoid bodies and endodermal cells [25], and epithelial ovarian cancer cell types [26]. The broad conclusion of these studies is that glycogene, and more specifically glycosyltransferase, expression measurements in a number of cases can semi-quantitatively predict corresponding enzyme activity and cell-surface glycan expression.…”
Section: Multi-level Regulation Of Glycosylationmentioning
confidence: 99%
“…In our MS analysis, glycans with terminal Glcs (glucose), which are usually related to glycoprotein quality control [25, 26] and exhibit higher expression in cancer [27, 28], were expressed more abundantly in SP cells. Increased hybrid N-glycans were detected in MP cells, indicating that the immediate products of GlcNAc transferase I were not further modified by other GlcNAc transferases.…”
Section: Discussionmentioning
confidence: 99%